A Resilient Subsistence Salmon Fishery in Southwest Alaska: A Case Study of Fish Camps in Nondalton - Holen, Davin (Journal of Northern Studies, 2010)
Harvesting and processing salmon is a significant subsistence activity for the residents of Nondalton, a predominantly Dena’ina Athabaskan community in Southwest Alaska. The Nondalton fishery, as a resilient social-ecological system, has had to adapt to change in order to maintain continuity over time. This paper will explore adaptation in a resilient salmon fishery through an ethnographic research project that documents the socio-cultural, economic, and environmental circumstances of fishing, mainly sockeye salmon (Oncorhynchus nerka), in the Kvichak Watershed of Southwest Alaska.